(untitled) (Research, Society and Development, 2021)
In an analysis of the themes leisure, youth and violence, the Study Group on Sociology and Pedagogy in Sport and Leisure at the Federal University of Minas Gerais investigated, using advanced search tools, on the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES) Database, the publications, from 2014 to 2019, that articulate these constructs. The objective was to present updated evidence about the theme and bring contextualized actions and reflections that include leisure of a young public. 11 articles were found when the search was for binomials. Being found 7 referring to leisure and youth and 4 - leisure and violence. GESPEL researchers conclude that the articles found – 58 of which were leisure, 4 were leisure and violence and 7 had the descriptors youth, violence, and examples of leisure experiences – are concentrated in researchers from sociology, psychology, cultural studies and little expression in leisure studies, which shows little contribution from researchers in the field of leisure who approach the articulation with youth and violence. However, all articles cited the three themes in some way, emphasizing the importance of developing dense studies on the subject, which is of great relevance in the contemporary world.